JAK-STAT Signaling in Autoimmunity and Cancer - Parveen S; Fatma M; Mir SS; Dermime S; Uddin S (ImmunoTargets and Therapy)
Sana Parveen,1,2 Mariyam Fatma,1,2 Snober Shabnam Mir,1,2 Said Dermime,3,4 Shahab Uddin1,5,6 1Department of Biosciences, Faculty of Science, Integral University, Lucknow, India; 2Molecular Cell Biology Laboratory, Integral Centre of Excellence for Interdisciplinary Research-4 (ICEIR-4) Integral University, Lucknow, India; 3Translational Cancer Research Facility, National Center for Cancer Care and Research, Hamad Medical Corporation, Doha, 3050, Qatar; 4College of Health Sciences, Qatar University, Doha, Qatar; 5Translational Research Institute & Dermatology Institute, Academic Health System, Hamad Medical Corporation, Doha, Qatar; 6Laboratory Animal Research Center, Qatar University, Doha, QatarCorrespondence: Shahab Uddin, Molecular Pathophysiology Core, Translational Research Institute, Academic Health System, Hamad Medical Corporation, Doha, Qatar, Tel +974 4025 3220, Email skhan34@hamad.qaAbstract: The JAK-STAT pathway is an essential cell survival signaling that regulates gene expressions related to inflammation, immunity and cancer. Cytokine receptors, signal transducer and activator of transcription (STAT) proteins, and Janus kinases (JAKs) are the critical component of this signaling cascade. When JAKs are stimulated by cytokines, STAT phosphorylation, dimerization, and nuclear translocation occur, which eventually impacts gene transcription. Dysregulation of JAK-STAT signaling is linked with various autoimmune diseases, including rheumatoid arthritis, psoriasis, and inflammatory bowel disease. This pathway is constitutively activated in human malignancies and leads to tumor cell survival, proliferation, and immune evasion. Oncogenic mutations in the JAK and STAT genes have been found in solid tumors, leukemia, and lymphoma. Targeting the JAK-STAT pathway is a viable and promising therapeutic strategy for the treatment of autoimmune diseases and cancers.Keywords: JAK-STAT pathway, inflammation, autoimmune diseases, cancer